2014
DOI: 10.1002/cssc.201402288
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Bipolar Membranes for Maintaining Steady‐State pH Gradients in Membrane‐Supported, Solar‐Driven Water Splitting

Abstract: A bipolar membrane can maintain a steady-state pH difference between the sites of oxidation and reduction in membrane-supported, solar-driven water-splitting systems without changing the overall thermodynamics required to split water. A commercially available bipolar membrane that can serve this purpose has been identified, its performance has been evaluated quantitatively, and is demonstrated to meet the requirements for this application. For effective utilization in integrated solar-driven water-splitting sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
145
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(152 citation statements)
references
References 32 publications
5
145
0
2
Order By: Relevance
“…[33] Bipolar membranes have been widely used in the electrodialysis industry for producing concentrated acid and base solutions and desalinating salt water, but solar-hydrogen devices that incorporate bipolar membranes were not modeled and evaluated experimentally until very recently. [33,45] A range of electrolyte combinations with different pH gradients exhibited sustainable solar-driven water-splitting reactions under steady-state conditions. A recent study with bipolar membranes has also shown that large-area (> 1 cm 2 ) III-V tandem photoabsorbers incorporating only earth-abundant electrocatalysts exhibited > 100 h of device stability at 10 % STH conversion efficiency, with a steady-state pH gradient of pH 9.3/pH 0.…”
Section: Membrane Separatormentioning
confidence: 99%
“…[33] Bipolar membranes have been widely used in the electrodialysis industry for producing concentrated acid and base solutions and desalinating salt water, but solar-hydrogen devices that incorporate bipolar membranes were not modeled and evaluated experimentally until very recently. [33,45] A range of electrolyte combinations with different pH gradients exhibited sustainable solar-driven water-splitting reactions under steady-state conditions. A recent study with bipolar membranes has also shown that large-area (> 1 cm 2 ) III-V tandem photoabsorbers incorporating only earth-abundant electrocatalysts exhibited > 100 h of device stability at 10 % STH conversion efficiency, with a steady-state pH gradient of pH 9.3/pH 0.…”
Section: Membrane Separatormentioning
confidence: 99%
“…Mallouk and colleagues and Freund, Lewis, and colleagues independently demonstrated that this behavior also occurred when liquid electrolytes were used. 4,5 They showed that BPMs wetted by aqueous acidic electrolyte on the CEL side and alkaline electrolyte on the AEL side supported and maintained pH differences across the membrane. In general, their reported theories and results were similar to those ofÜnlü, Zhou, and Kohl; however, use of a liquid electrolyte allowed the potential difference across the membrane to be measured selectively using four-electrode electrochemical techniques, 6 which are analogous to solid-state four-point-probe methods.…”
mentioning
confidence: 99%
“…The data obtained under reverse-bias conditions resembled that reported previously in the literature; E BPM_SCE = 798 ± 5 mV using two SCEs, which is close to the value of ∼0.83 V calculated using Equation 1. 5,9 Assuming the BPM equilibrated with the liquid electrolytes, by definition the electrochemical potential difference across the membrane would be zero. Because E BPM_SCE was non-zero, it suggests the SCEs do not sense the electrochemical potential difference and instead only sense the electric potential difference, 3 which is equal in magnitude but opposite in sign to the chemical potential difference that is not being sensed.…”
mentioning
confidence: 99%
“…Carbon dioxide is reduced at a Pd/C-coated Ti mesh cathode in close to neutral solution (2.8 M HCO 3 − , pH = 8.0) exposed to 1 atm of CO 2 gas. The bipolar membrane [17][18][19][20] allows to maintain the large pH difference of the cell under continuous operation at a light-limited photocurrent density of 8.5 mA cm −2 and > 94% Faradaic efficiency for CO 2 reduction to formate [15] . Modest voltage loss of 480 mV at the bipolar membrane and low overvoltages for CO 2 reduction ( < 100 mV) and O 2 evolution (320 mV) enable a remarkable 10% energy conversion efficiency.…”
Section: Silica Nanolayers With Embedded Molecular Wires For Artificimentioning
confidence: 99%